Studies on Physico-Chemical, Sensory and Microbiological Quality of Kinnow Juice Blends under Refrigerated Storage - R L Bhardwaj (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
Various fruit juice blends were prepared as (i) Kinnow juice:Aonla juice:Ginger juice in 100:0:0; 95:5:0; 92:5:3 ratios and Kinnow juice:Pomegranate juice:Ginger juice in 90:10:0; 87:10:3 ratios for improving flavour, palatability, nutritive value and medicinal value. The juice blends were preserved by pasteurization at 75°C or 85°C for 15 minutes, and, by adding potassium meta-bisulphite (KMS) at 500 or 750 ppm. These blends were stored in 200ml colourless glass bottles under refrigerated conditions (4±1°C) for six months and tested at three month intervals for physicochemical sensory quality and microbial population. Individual effect of juice blending ratio, processing temperature and KMS treatment was found to be significant for prolonging storage life and for maintaining an acceptable quality of the juice blends. The blend of Kinnow:Pomegranate:Ginger juice at 87:10:3 ratio, followed by Kinnow:Aonla:Ginger juice @ 92:5:3, processed at 75°C for 15 min with 750 ppm KMS, was the most effective for obtaining superior physico-chemical and sensory quality of the blend. However, minimum microbial population was recorded in the juice processed at 85°C (and not 75°C) with the same treatment combination.